2016
DOI: 10.1007/s10719-016-9692-0
|View full text |Cite
|
Sign up to set email alerts
|

Dicarbonyl stress in clinical obesity

Abstract: The glyoxalase system in the cytoplasm of cells provides the primary defence against glycation by methylglyoxal catalysing its metabolism to D-lactate. Methylglyoxal is the precursor of the major quantitative advanced glycation endproducts in physiological systems - arginine-derived hydroimidazolones and deoxyguanosine-derived imidazopurinones. Glyoxalase 1 of the glyoxalase system was linked to anthropometric measurements of obesity in human subjects and to body weight in strains of mice. Recent conference re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 73 publications
2
63
0
Order By: Relevance
“…Masania et al reported higher fasting serum levels of MG and D-lactate in subjects with obesity compared to non-obese adults following an isocaloric diet for 2 weeks (26). These findings are in line with the current literature suggestive of plasma D-lactate level as a surrogate marker for MG flux, which is increased in obesity (26,(32)(33)(34). Furthermore, in a cross-sectional study, we previously demonstrated that serum D-lactate levels were higher in obese Latino adolescents and correlated with serum triglycerides and small dense LDL levels (27).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Masania et al reported higher fasting serum levels of MG and D-lactate in subjects with obesity compared to non-obese adults following an isocaloric diet for 2 weeks (26). These findings are in line with the current literature suggestive of plasma D-lactate level as a surrogate marker for MG flux, which is increased in obesity (26,(32)(33)(34). Furthermore, in a cross-sectional study, we previously demonstrated that serum D-lactate levels were higher in obese Latino adolescents and correlated with serum triglycerides and small dense LDL levels (27).…”
Section: Discussionsupporting
confidence: 92%
“…The limit of detection was 1 µmol/L, and the reaction was linear up to 15 µmol/L. To further ensure specificity, we ran the reaction with and without 1 mmol/L L-lactate (upper limit of reference range in serum) and found <5% interference (p < 0.05), in agreement with data on the literature (26,28). The intraassay coefficient of variation was 5% at 2 µmol/L and 3% at 10 µmol/L.…”
Section: De Novo Lipogenesis Insulin Sensitivity and D-lactatesupporting
confidence: 84%
See 2 more Smart Citations
“…This effect is lost when marked increase in protein glycation, oxidation and nitration in the joints in advanced disease outweighs the effects of increased protein residence time at interstitial sites. Albumin TER has been described previously as a confounding factor in the diagnostic use of plasma protein glycation [52]. …”
Section: Discussionmentioning
confidence: 99%